EXPLORING INNOVATIVE APPROACHES TO TEACHING ENGLISH AS A SECOND LANGUAGE (ESL) - qizi, Meliqo’ziyeva Farangiz G’iyosiddin (Journal of Higher Education and Academic Advancement, 2024)
This paper investigates the pivotal role of English as a global lingua franca and the necessity for innovative methodologies in teaching English as a second language (ESL). General background: In an increasingly interconnected world, proficiency in English is essential for effective communication, career opportunities, and access to information. Specific background: Traditional teaching methods often focus on rote memorization and passive learning, which can hinder active language acquisition and fail to engage learners meaningfully. Knowledge gap: Despite advancements in language education research, there remains a lack of widespread implementation of innovative teaching strategies that foster active engagement. Aims: This study aims to highlight contemporary methodologies that enhance ESL instruction and provide practical solutions for educators. Results: The findings suggest that innovative approaches, such as communicative language teaching, task-based learning, and technology integration, significantly improve learner motivation, interaction, and language retention. Novelty: By presenting evidence from current research and case studies, this paper offers a fresh perspective on effective ESL teaching practices. Implications: The insights gained from this study underscore the need for educators to adapt their instructional strategies to better meet the diverse needs of language learners, ultimately contributing to more effective and engaging ESL education. The paper advocates for a paradigm shift in language teaching to embrace innovative methods that foster active, lifelong language learning.